Effect of Mutations in VP5* Hydrophobic Loops on Rotavirus Cell Entry - Kim, Irene S. (American Society for Microbiology (ASM), 2010)
Experiments in cell-free systems have demonstrated that the VP5* cleavage fragment of the rotavirus spike protein, VP4, undergoes a foldback rearrangement that translocates three clustered hydrophobic loops from one end of the molecule to the other. This conformational change resembles the foldback rearrangements of enveloped virus fusion proteins. By recoating rotavirus subviral particles with recombinant VP4 and VP7, we tested the effects on cell entry of substituting hydrophilic for hydrophobic residues in the clustered VP5* loops. Several of these mutations decreased the infectivity of recoated particles without preventing either recoating or folding back. In particular, the V391D mutant had a diminished capacity to interact with liposomes when triggered to fold back by serial protease digestion in solution, and particles recoated with this mutant VP4 were 10,000-fold less infectious than particles recoated with wild-type VP4. Particles with V391D mutant VP4 attached normally to cells and internalized efficiently, but they failed in the permeabilization step that allows coentry of the toxin α-sarcin. These findings indicate that the hydrophobicity of the VP5* apex is required for membrane disruption during rotavirus cell entry.